A Quantitative Investigation Toward Halal Cosmetics Products : Theory of Plan Behavior - Wati, Rahma (Quantitative Economics Research, 2019)
Nowadays, halal cosmetics growing rapidly in muslim countries. Halal is not only a religious issue but also is an opportunity to increase sale and acquire competitive advantage. This research explores to exert theory of planned behavior knowing the young consumer attitude for intention to buy halal cosmetics product. The framework of young consumer attitude in this research is based on the Ajzen?s Theory of Planned Behavior which postulates three conceptually independent determinants of behavioral intention consist of attitude, subjective norm and perceived behavioral control. Data were collected through young consumer in Malang City and the respondent between 15 to 25 years old. The findings of the research revealed young consumer attitude and perceived behavior control have significant relationship for intention to buy halal cosmetics product. However, subjective norm have less significant if compared with attitude and perceived behavior control of young consumer in choosing halal cosmetics product. This research suggest that to increase young consumer attitude toward halal cosmetics product the company should make integrated marketing strategy to raise consumer awareness toward halal cosmetics product. For future research may take a look the framework of theory planned behavior which is consist three conceptually independent in the different geographical location in other side of Indonesia.